ANALISIS CEMARAN LIMBAH INDUSTRI DAN DOMESTIK TERHADAP BIOTA LAUT DI PERAIRAN KOTA TANJUNGPINANG, PROVIPNSI KEPULAUAN RIAU - Susanto, Agus; Pratomo, Hurip; Rahman, Arief (Center for Environmental Technology, 2015)
Industrial sector is the second priority in development of Tanjungpinang city. The mining industry, processing industry, transport and food are thriving . People has the opinion that a small industry is an industry that does not threaten the environment, so that the small-scale industrial waste are sometimes were forgotten due to it is not significant, and not too dangerous, whereas the B3 waste contained in domestic waste can cause disturbance of marine life and the ecosystem this will have potential to destroy the ecosystem. This study aims to explain the impact of B3 and domestic waste pollution to the environment, especially marine waters to marine life, and feedback to the provincial government for the formulation strategy of the management of the Tanjungpinang waters environment. For the analysis, 10 water samples and 15 aquatic biota was taken at different locations. While the quantitative analysis of pollutants carried by observing a population of the elements of hazardous substances from sediment samples, water and biota network. XRF techniques (X-Ray Fluorescence) and AAS (Atomic Absorbance Spectroscopy) used for the analysis content of the samples. The pollution index determined by compare metal concentration ratio the polluted areas with the standard metal concentration areas that were not polluted. The results show that the coastal water of tanjungpinang have been contaminated by heavy metals (As, Cd, Cu , Pb, Zn, and Ni) with pollution index 2.91 - 5.96. The pollutant Metals were came from the human activities in the shipbuilding industry usually Pb and Zn which is the main component of the paint. While heavy metals such as arsenic (As), Cadmium (Cd), copper (Cu) probably derived from bauxite mining activity, the high levels of nitrate is a sign of agricultural activities that use fertilizers. Unfortunately the rest of it discharged into the coastal waters of Tanjungpinang city, and there is also pollution of E-coli from human waste. Biota that live in the waters of Tanjungpinang have been contaminated by heavy metals (Hg, Zn, and Ar) by bioaccumulation. The related activity of the pollutant was the bauxite processing industry in the past. Heavy metal pollution is highest in Kijing (Pilsbryoconcha exillis) which includes : Hg, Cr, As, Cu, Zn, Ni, and the dimersal fish that have limited movement. Feedback given is that provincial governments do mangrove reforestation along the coast and estuaries, and create marine conservation areas determination of areas (KKLD) in the strait Dompak water.Ã‚Â Key Words : heavy metals, marine life, coastal water of tanjungpinang, mangrove